Anti‐inflammatory therapy with tumour necrosis factor inhibitors is associated with reduced risk of major adverse cardiovascular events in psoriasis. (1st May 2018) - Wu, J.J.; Joshi, A.A.; Reddy, S.P.; Batech, M.; Egeberg, A.; Ahlehoff, O.; Mehta, N.N.
Abstract: Background: Psoriasis is a systemic chronic inflammatory condition associated with increased risk of cardiovascular disease. Data demonstrating that decreased skin inflammation reduces cardiovascular events in patients with psoriasis may be generalizable to other chronic inflammatory states with heightened cardiovascular risk. Objective: To determine whether tumour necrosis factor inhibitor (TNFi) therapy is associated with decreased major adverse cardiovascular events (MACE) in patients with psoriasis. Methods: In this retrospective cohort study using the KPSC health plan, patients had at least three ICD‐9 codes for psoriasis and no antecedent MACE codes. Propensity score‐adjusted multivariable Cox regression assessed hazard ratios (HR) of MACE associated with TNFi use. Results: After adjusting for cardiovascular risk factors, the TNFi cohort had significantly lower MACE HR compared with the topical cohort (HR, 0.80; 95% CI, 0.66–0.98). The oral/phototherapy cohort had similar MACE HR compared with the topical cohort (HR, 1.19 (95% CI, 0.99–1.42)). Conclusions: We observed significantly lower MACE risk in patients with psoriasis receiving TNFi compared to topical or oral/phototherapy agents. TNFi therapy may have benefits beyond skin disease in mitigating cardiovascular event risk.